Effect of melatonin intake on oxidative stress biomarkers in male reproductive organs of rats under experimental diabetes - Gobbo, Marina G. [UNESP]; Pereira Costa, Carolina F. [UNESP]; Humberto Silva, Danilo G. [UNESP]; Almeida, Eduardo A. de [UNESP]; Goes, Rejane M. (Hindawi Publishing Corporation, 2015)
This study investigated the antioxidant system response of male reproductive organs during early and late phases of diabetes and the influence of melatonin treatment. Melatonin was administered to five-week-old Wistar rats throughout the experiment, in drinking water (10 mu g/kg b.w). Diabetes was induced at 13 weeks of age by streptozotocin (4.5 mg/100g b.w., i.p.) and animals were euthanized with 14 or 21 weeks old. Activities of catalase (CAT), glutathione-S-transferase (GST), glutathione peroxidase (GPx), and lipid peroxidation were evaluated in prostate, testis, and epididymis. The enzymes activities and lipid peroxidation were not affected in testis and epididymis after one or eight weeks of diabetes. Prostate exhibited a 3-fold increase in GPx activity at short-term diabetes and at long-term diabetes there were 2- and 3-fold increase in CAT and GST, respectively (p <= 0.01). Melatonin treatment to healthy rats caused a 47% increase in epididymal GPx activity in 14-week-old rats. In prostate, melatonin administration normalized GST activity at both ages and mitigated GPx at short-term and CAT at long-term diabetes. The test is and epididymis were less affected by diabetes than prostate. Furthermore, melatonin normalized the enzymatic disorders in prostate demonstrating its effective antioxidant role, even at low dosages.